Adjuvantes na deriva de 2,4-D + glyphosate em condições de campo - Costa, Augusto Guerreiro Fontoura; Velini, Edivaldo Domingues [UNESP]; Rossi, Caio Vitagliano Santi; Corrêa, Marcelo Rocha; Negrisoli, Eduardo; Fiorini, Marcus Vinicius; Siono, Luis Marcelo [UNESP] (Universidade Federal de Santa Maria, 2014)
The aim of the research was to evaluate the effect of adjuvants on the spray drift applications from mixture of 2,4-D + glyphosate. The trial was carried out in field conditions in a completely randomized design. The treatments corresponded to solutions containing mixture of the herbicides 2,4-D + glyphosate (670 and 1068g ha-1, respectively) adding the adjuvants (v v-1): mineral oil (0.5%); anti-drift agent (0.09%); spreader-sticker A (0.1%); liquid fertilizer (0.05%); spreader-sticker B (0.25%); and only herbicides without adjuvantes (control). Nylon strings were used to drift determination outside the application area (1, 5, 10, 20, 50, 100 and 200 m away) with 4 replications and six foam cylinders placed on the boom of the sprayer were used to collect the droplets subject to drift. The applications were performed simultaneously, using a specific salt tracer for each spray solution to quantify the deposits by spectrophotometer. It was not possible to verify effect of the adjuvants on drift at different distances of the application area. Based on droplets collected above the boom spray, it was found that susceptibility to drift was lower with the mineral oil and the anti-drift agent. The drift risk was higher with the liquid fertilizer and the spreader-sticker B.

O objetivo do trabalho foi avaliar o efeito de adjuvantes sobre a deriva em aplicações da mistura de 2,4-D + glyphosate. O experimento foi conduzido em condições de campo em delineamento inteiramente casualizado. Os tratamentos corresponderam às soluções com a mistura dos herbicidas 2,4-D + glyphosate (670 e 1068g ha-1, respectivamente) adicionando-se os adjuvantes (v v-1): óleo mineral (0,5%); agente antideriva (0,09%); espalhante adesivo A (0,1%); fertilizante líquido (0,05%); espalhante adesivo B (0,25%); e somente os herbicidas (testemunha). Foram utilizados para determinação de deriva fios de náilon externos à área de aplicação (1, 5, 10, 20, 50, 100 e 200m de distância) com quatro repetições e seis cilindros de espuma posicionados sobre a barra do pulverizador para coleta de gotas sujeitas à deriva. As aplicações foram realizadas simultaneamente, utilizando-se um sal traçador específico em cada solução de aplicação para quantificar os depósitos por meio de espectrofotômetro. Não foi possível verificar efeito dos adjuvantes sobre a deriva nas diferentes distâncias da área de aplicação. Com base nas gotas coletadas acima da barra de pulverização, constatou-se que a suscetibilidade à deriva foi menor com o óleo mineral e o agente antideriva. O risco de deriva foi maior com o fertilizante líquido e o espalhante adesivo B.
Adjuvants on spray drift of 2,4-D + glyphosate in field conditions
Keywords: herbicida; coletor de deriva; pulverizador de barra; aditivo; herbicide; drift collector; boom sprayer; additive